Vascularized Bone Grafts for Spinal Fusion—Part 2: The Rib. Issue 5 (20th February 2021) - Reece, Edward M; Agrawal, Nikhil; Wagner, Kathryn M; Davis, Matthew J; Abu-Ghname, Amjed; Shekher, Rohil; Raber, Michael R; Winocour, Sebastian; Bohl, Michael A; Ropper, Alexander E
Abstract: BACKGROUND: Pseudoarthrosis, or failure to achieve bony union, is a well-known complication of spinal fusion operations. Rates range from 5% to 40% and are influenced by both patient and technical factors. Patients who do not achieve complete fusion may experience a return or worsening of their preoperative pain. For patients with complicated pathologies, vascularized bone grafts (VBGs) have been shown to provide better outcomes than nonvascularized bone grafts (N-VBGs). OBJECTIVE: To enhance an instrumented spinal fusion by the innovative technique presented herein that utilizes a rotated, pedicled VBG from the left eighth rib under the paraspinous musculature into the midlumbar posterolateral gutter. METHODS: For posterior approaches, the rib can be easily accessed and rotated into the appropriate strut position. The rib is dissected out, identifying and preserving the neurovascular bundle medially. The rib is then tunneled medially and appropriately positioned as the spinal graft, with the curve providing anatomic kyphosis or lordosis, depending on the surgical location. It is then successfully fixated with plates and spinal screws. RESULTS: In our limited experience to date, vascularized rib grafting procedures augment fusion and reduce operating room time and bleeding compared to free flap procedures. No patients have experienced complications related to these grafts. CONCLUSION: Pedicled vascularized rib grafts can be utilized to provide the advantages of a vascularized bone flap in complicated pathologies requiring spinal fusion as far as the L2-L3 level, without the morbidity associated with free tissue transfer.